A study of temporal price efficiency of food grain marketing in north eastern Nigeria - Nuhu, H.; Amaza, P.; Gaya, H. (2006)
The study examined temporal aspect of marketing efficiency in urban marketing system for sorghum and cowpea in North-eastern Nigeria. The data for the study were obtained through the use of structured questionnaires, interview and market surveys on storage cost. Four markets (Maiduguri, Damaturu, Gombe and Yola) known for the marketing of Cereal grains and pulses were selected purposively for the study. Thirty questionnaire were distributed randomly to marketers in the selected markets. Secondary data coverd wholesale monthly price for 60 months. The analyse tool used was the temporal pricing model. Emperical findings indicates that most of the results were less than the cost of storing grains, except for cowpea where the average not seasonal increase was greater than expected price most of the time, at Gombe market for instance, in 2000, cowpea was 12% greater than the expected price and 35% in 2001. This seems to suggest that inflation, poor storage as well as lack of price information might have been the cause. Some suggestions are made for improving marketing performance.